Difficulties and Concerns Regarding International Displacement Laws (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This article offers a thorough analysis of forced migration, emphasizing its intricate and ever-changing characteristics, with a particular emphasis on the difficulties encountered by internally displaced people (IDPs) in India. This statement highlights the shortcomings of current legal systems and emphasises the pressing need for specific laws to cater to the distinct requirements of internally displaced persons (IDPs). It underscores the dangers associated with a lack of responsibility and the wide powers held by the government. The paper examines the historical and philosophical dimensions of global displacement laws, highlighting the significance of international cooperation and regional organisations, such as the African Union, in complementing current institutions. The text explores the economic, social, and psychological effects of relocation and argues for comprehensive approaches to tackle the difficulties experienced by displaced individuals. This analysis explores the involvement of the United Nations in displacement, acknowledging its capacity to operate both proactively and as a supportive entity, despite challenges posed by global politics and institutional deficiencies. The thesis explores India's legal framework pertaining to human displacement, emphasizing the intricate equilibrium that courts must maintain between constitutional principles, national security considerations, and international commitments. As a conclusion, the paper advocates for a thorough approach to tackle the intricacies of displacement, with a focus on worldwide cooperation, legal frameworks, and acknowledging the distinct requirements of displaced persons within the wider discussion on immigration, asylum, and humanitarian assistance. This abstract enhances the existing discourse on forced migration by emphasizing the significance of collaborative endeavours and all-encompassing strategies at both domestic and global scales.